2021
DOI: 10.3389/fneur.2021.745265
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Sequela of Acute Pesticide Poisoning Among Adults in Central Taiwan

Abstract: Background and Purpose: Cases of acute pesticide poisoning account for significant morbidity and mortality in developing countries; however, its burden in Taiwan remains unknown. The study examined acute pesticide poisoning (APP) involving adults in the central region of Taiwan, which is a mainly agricultural sub-urban area.Methods: The retrospective study evaluated the outcome and neurological sequelae of patients with APP in a Taiwanese cohort between April 2002 and February 2019. The pesticides were classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…Neither pesticide nor Ciguatera poisoning are common in Germany and neither of the two studies investigated poisoning induced OHCA. 3 So, the cited studies investigate cohorts with almost no overlap to our study population and are not in the least contradicting the good neurologic outcome of 15% in P-OHCA in our study.…”
Section: To the Editorcontrasting
confidence: 44%
“…Neither pesticide nor Ciguatera poisoning are common in Germany and neither of the two studies investigated poisoning induced OHCA. 3 So, the cited studies investigate cohorts with almost no overlap to our study population and are not in the least contradicting the good neurologic outcome of 15% in P-OHCA in our study.…”
Section: To the Editorcontrasting
confidence: 44%
“…Besides carbon monoxide poisoning, previous studies have demonstrated that neurological manifestations were the common clinical complications among survivors suffering from other poisons including food poisoning and pesticide poisoning. 4,5 For all these reasons, we are not aware of a biological nor toxicological rationale to support these statistical results, and the results may also be related to paradoxical fitting of the logistic model. Thus, we suggest that the author include more valuable variables (e.g., frailty, comorbidities, laboratory markers, etc.)…”
Section: To the Editormentioning
confidence: 97%